Подводно-археологические исследования на Черноморском шельфе Южного берега Крыма в 2008—2009 гг. - Герасимов, В.Е. (Археологічні дослідження в Україні, 2010)
In 2008 and 2009, the International Underwater Group of the Crimean Intercomplex Archaeological Expedition of the Crimean branch of the IA NASU conducted the underwater archaeological prospecting of the Black Sea shelf of the southern coast of the Crimea on the territory of Alushta and Yalta city councils. Sites of anchorages and shipwrecks of the Mediaeval period, as well as lots of materials of Ancient and Mediaeval times were found.